Gestión administrativa - operativa y su incidencia en la productividad de la corporación la Pepa de Oro, del Cantón Vinces, Periodo 2013-2014. Manual de Gestión - Quinto Mora, Gloria Verónica (2016)
Currently the administrative management represents an important role in the activities undertaken by a company, with the support of development techniques that help efficiently and timely to achieve results in customer satisfaction. This research was conducted at the Corporation's Pepa de Oro, which is located in the city of Vinces, Los Rios Province, is a corporation formed by 13 peasant organizations whose mission focuses on working to strengthen relationships and socioeconomics of grassroots organizations that comprise it. The main objective of the research was to analyze the incidence of administrative management in the productivity of the corporation. The research methodology is divided into three phases, the first a review of the organizational structure of the company was done through visits to offices, warehouses and plants; in the second phase interviews was applied to the president and treasurer of the corporation and in the last phase surveyed directory organization. The results show that the Corporation is divided into three business units: Commercial Caco, Piladora and Chocolate Factory, the directors of the Corporation is composed of the members, the same who are elected by voting in general meeting; high weakness in the control and management of each business unit due to the absence of administrative tools that directly affects the productivity level of evidence.